2005
DOI: 10.4049/jimmunol.175.1.541
|View full text |Cite
|
Sign up to set email alerts
|

Mannose-Binding Lectin Is a Regulator of Inflammation That Accompanies Myocardial Ischemia and Reperfusion Injury

Abstract: The mannose-binding lectin (MBL), a circulating pattern recognition molecule, recognizes a wide range of infectious agents with resultant initiation of the complement cascade in an Ab-independent manner. MBL recognizes infectious non-self and altered self in the guise of apoptotic and necrotic cells. In this study, we demonstrate that mice lacking MBL, and hence are devoid of MBL-dependent lectin pathway activation but have fully active alternative and classical complement pathways, are protected from cardiac … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
215
2
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 217 publications
(233 citation statements)
references
References 47 publications
15
215
2
1
Order By: Relevance
“…MBL may enhance inflammation-mediated tissue injury during postischemic reperfusion by complement activation (14)(15)(16). MBL has also been suggested to be a mediator in the pathogenesis of microvascular complications in type 1 diabetes (36) as well as graft survival after kidney transplantation (37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MBL may enhance inflammation-mediated tissue injury during postischemic reperfusion by complement activation (14)(15)(16). MBL has also been suggested to be a mediator in the pathogenesis of microvascular complications in type 1 diabetes (36) as well as graft survival after kidney transplantation (37).…”
Section: Discussionmentioning
confidence: 99%
“…Lack of functional alleles in some populations is associated with increased risk of atherosclerosis and cardiovascular occlusion (9)(10)(11)(12)(13). However, experimental data and clinical observations suggest that MBL and the lectin pathway of complement may initiate the inflammatory reaction seen in relation to ischemia reperfusion injury (14)(15)(16). Moreover, subjects who are homozygous for the functional MBL2 genotype and have high serum levels of MBL have the highest rate of early restenosis after carotid eversion endarterectomy (17).…”
mentioning
confidence: 99%
“…However, MBL plays a dual role in modifying inflammatory responses to injury [34]. Mice that lack MBL, and hence are devoid of MBL-dependent lectin pathway activation but have fully active alternative and classical complement pathways, are protected from cardiac reperfusion injury with resulting preservation of cardiac function [35]. In fact, variant MBL alleles that cause dominant low-serum concentrations have high frequencies in all populations studied; therefore, low MBL concentrations may confer selective advantages on individuals carrying the variant alleles [34].…”
Section: Discussionmentioning
confidence: 99%
“…A study (35) in a stroke model also found that the powerful neuroprotective action of C1 inhibitor (C1-INH) on brain I/R injury does not require C1q, an early component in the classical pathway of complement. Recently, Stahl and colleagues (36,37) reported that MBL-deficient mice displayed limited injury in the intestinal or myocardial I/R models. They showed that C2-knockout, but not C1q-deficient, mice were protected in the intestinal I/R model (36).…”
Section: Activation Of the Lectin Pathway By Natural Igm In A Modelmentioning
confidence: 99%